The teaching and learning process of quadratic function with the Winplot software aid in high school - Mendes, Felipe (2018)
In this article, we present the results of the analysis and reflection on the use of information and communication technologies in the teaching and learning process of the quadratic function in High School, using the free software Winplot. In addition, a brief historical and theoretical study of the use of technologies for educational purposes is made. Through this study, which was part of a research of a specialization course in Mathematics Teaching, a lesson plan was developed and applied in a class of the 1st year of High School, which included activities in which Students should sketch the graphs of the functions in the software and, from the observation and analysis of the plots made, highlight the behavior of the functions and arrive at general conclusions that serve for all quadratic functions. In the development of this work, it was possible to show the importance and the duty of the school and the teacher to introduce the technologies in the teaching and learning process of Mathematics, either to make the classes more attractive and interesting to the students, These, when interacting with an educational software, manage to reach the conclusions objectified through the analysis of the material generated in the computational program.